Genotyping of rice (Oryza sativa L.) plants according to their root distribution pattern and their tolerance to drought - Novitasari, Adin; Rumanti, Indrastuti Apri; Wening, Rina Hapsari; Damanhuri, Damanhuri (Jurnal Ilmu Pertanian, 2023)
Drought condition is one of the major problems in producing rice in Indonesia. In plant breeding, selection is the main step to create superior varieties. An indicator of drought stress-tolerant rice varieties is the root distribution pattern because it describes the behavior of the roots in searching for water for photosynthesis and metabolism processes. One of the morphological traits related to drought tolerance in rice is root growth and development. This study aimed to determine the morphological and anatomical characteristics of drought-tolerant rice roots and identify drought-tolerant genotypes. The experiments were arranged in a factorial randomized block design with four replications. The first factor was genotype, consisting of ten genotypes. The second factor was drought stress, consisting of two environments without drought and with drought stress. Drought was given only in the vegetative phase, i.e., 1–14 days after planting. WINDEX analysis was performed to determine rice drought tolerance and identify drought-tolerant genotypes. The results showed that three out of the ten tested genotypes had higher WINDEX values, namely BP30411f (7.62), B13983-KA-6-3 (7.99), and BP29790d-PWK-2-SKI-1-3 (9.25). Based on the root distribution pattern, plants with longer primary root lengths, more seminal roots, longer seminal root lengths, and high root angles were predicted to be drought tolerant characteristics. Selection of these characters could be used in future rice breeding programs to obtain plants with superior genotypes.